S58 Beta-Catenin determines tracheal cell fate and squamous lung cancer progression by modulating intercellular adhesiveness. (2nd December 2011) - Giangreco, A; Lu, L; Vickers, C; Ilieva, E; Groot, K; George, J; Nicholson, A; Sage, E; Watt, F; Janes, S
Abstract : Human lung cancers including squamous cell carcinoma (SCC) are a leading cause of death, and while evidence suggests that basal stem cells drive SCC initiation and progression, the mechanisms regulating these processes remain unknown. In this study we show that β-catenin signalling regulates basal stem cell fate and subsequent SCC progression. In a cohort of preinvasive SCCs we established that elevated basal stem cell β-catenin signalling is positively associated with increased disease severity, epithelial proliferation, and reduced intercellular adhesiveness. We demonstrate that transgene-mediated β-catenin inhibition within keratin 14-expressing basal stem cells delayed normal airway repair while basal cell-specific β-catenin activation increased cell proliferation, directed differentiation, and promoted an epithelial-to-mesenchymal transition (EMT) that included increased Snail transcription and reduced E-cadherin-mediated adhesiveness. These effects were recapitulated in normal human bronchial epithelial cells in vitro following both pharmacological β-catenin activation and E-cadherin inhibition, and mirrored our findings in preinvasive SCCs. Overall this data shows that airway stem cell β-catenin modulates cell adhesiveness to determine cell fate and its mis-expression is a key step in the development of human lung cancer.